Reconstruction of Ius Constituendum Cyber Notary Regulations in E-RUPS as Relaas Acta - Shicilya, Wanda; Souissa, Marsella Maurin; Kusuma, Rizka Tiara; Wesna, Putu Ayu Sriasih (Sultan Agung Notary Law Review, 2024)
The purpose of this study is to examine the reconstruction of the ius constituendum regulating cyber notary in E-RUPS as a relaas acta with 2 problems, namely the urgency of regulating cyber notary as the legal basis for making E-RUPS and the draft ius constituendum regulating cyber notary in the future. This study uses a normative legal research method in the form of a legislative approach. The results of the study indicate that there is uncertainty in the legal regulation of cyber notary in Indonesia regarding E-RUPS whose deeds are made by a notary as a relaas acta, so a draft legislation is needed as a legal basis for cyber notary in the future to guarantee the validity of an authentic deed.